Hubungan Kontrol Sosial Orang Tua dengan Perilaku Seks Pranikah Remaja Kelurahan Batang Arau Kecamatan Padang Selatan - Fatri Hanifah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2013)
The reality, premarital sexual behavior almost increased every year in adolescents. The adolescents assumed that do activity of sex with homosexual or heterosexual likes daily activity, thereby they will feel degradation in social norm of adolescent itself. In this case, role of parents are very important to give strong social control through of education, protection, controling, and reinforcement the social norm in order that adolescents were avoided from premarital sexual behavior. Therefore, this research purposed to reveal how the relationship between social control of parents with premarital sex behavior in adolescents. This research used a quantitative of metode with kind the correlational of description. The result in this research was can get a not significant relationship between social control of parents with premarital sexual behavior in adolescents, it means that social control parents was not always influence premarital sexual behavior of adolescents. So that the parents must found the other factor to influence of premarital sexual behavior in adolescents to protected the adolescents from premarital sexual behavior.